2010
DOI: 10.18352/bmgn-lchr.216
|View full text |Cite
|
Sign up to set email alerts
|

Blanket strategy: A response of environmental groups to the globalising forest industry

Abstract: Globally, in recent decades, forest industry has come under increased scrutiny, often led by environmental non-government organisations (ENGOs). The present paper analyses the strategies used by the ENGOs in different forest conflicts involving forest industry. The main aim is to determine if there is a relationship between forest industries' partners (shareholders, financiers and customers) and the location of the ENGOs campaigning against them. Fourteen forest conflicts are used as case studies, representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Therefore as the groups are attempting to shape public opinion as well as cultural practices (King, 2008), it could be seen that media coverage is a goal as well as a tool. Gritten and Mola-Yudego (2010) found that ENGOs targeting forestry companies were greatly influenced by the potential media coverage that the campaign would garner, including considering the profile of the company as well as its location (considering the environmental and social impact of the company's operations). The same authors also found that international media coverage of forest conflicts was relatively low, even if the conflict was intense or had a great deal of potential negative impact (Gritten et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore as the groups are attempting to shape public opinion as well as cultural practices (King, 2008), it could be seen that media coverage is a goal as well as a tool. Gritten and Mola-Yudego (2010) found that ENGOs targeting forestry companies were greatly influenced by the potential media coverage that the campaign would garner, including considering the profile of the company as well as its location (considering the environmental and social impact of the company's operations). The same authors also found that international media coverage of forest conflicts was relatively low, even if the conflict was intense or had a great deal of potential negative impact (Gritten et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades forest industry around the world has come under increased scrutiny from environmental non-governmental organisations (ENGOs) such as Friends of the Earth (FoE) and Greenpeace (Gritten and Mola-Yudego, 2010). ENGO scrutiny has at times greatly impacted the industry's operating practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Australian forest plantation industry manages a significant area of land, and is subject to significant social pressure, linked to a range of social concerns about whether company practices such as chemical use (Schirmer, 2007), and plantation development have negative impacts on rural communities (Barlow and Cocklin, 2003;Schirmer, 2002). The forest sector receives criticism in literature, the media (Dare et al, 2011a), and from various stakeholders who argue that forest companies act unsustainably or irresponsibly (Gritten and Mola-Yudego, 2010).…”
Section: Introductionmentioning
confidence: 99%